Analisis Praktik Transparansi dan Akuntabilitas pada Operasional Bidang Keuangan Polda XYZ (Lembaga Pengembangan Kinerja Dosen, 2025)
This study is based on the urgency of applying the principles of transparency and accountability in law enforcement institutions, particularly the Indonesian National Police. The Finance Division (Bidkeu) of Polda XYZ plays a central role in managing, supervising, and ensuring accountability for the use of public funds, making it essential to examine the extent to which good governance principles have been implemented. The research employed a qualitative approach with a case study design. Primary data were obtained through participatory observation and semi-structured interviews during field practice, while secondary data came from official regulations, financial reports, and relevant academic references. Data analysis was conducted using thematic techniques to categorize information into three key aspects: transparency, accountability, and implementation challenges. Findings indicate that transparency is reflected in the re-recording of evidence balances, adjustment of financial archives, and completion of workload analyses. Accountability appears in multi-layered financial report reviews and digital-based activity reporting. Nonetheless, barriers such as limited access to sensitive data, lengthy bureaucratic procedures, and minimal knowledge transfer remain. Overall, transparency and accountability practices are in place but require strengthening through digital systems and capacity building.